Genesis and maintenance of "Mediterranean hurricanes" - K. Emanuel (Advances in Geosciences, 2005)
Cyclonic storms that closely resemble tropical cyclones in satellite images occasionally form over the Mediterranean Sea. Synoptic and mesoscale analyses of such storms show small, warm-core structure and surface winds sometimes exceeding 25ms-1 over small areas. These analyses, together with numerical simulations, reveal that in their mature stages, such storms intensify and are maintained by a feedback between surface enthalpy fluxes and wind, and as such are isomorphic with tropical cyclones. In this paper, I demonstrate that a cold, upper low over the Mediterranean can produce strong cyclogenesis in an axisymmetric model, thereby showing that baroclinic instability is not necessary during the mature stages of Mediterranean hurricanes.